2023
DOI: 10.3390/plants12071548
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Reproductive Stage-Waterlogging on the Growth and Yield of Upland Cotton (Gossypium hirsutum)

Abstract: The reproductive stage of cotton (Gossypium sp.) is highly sensitive to waterlogging. The identification of potential elite upland cotton (Gossypium hirsutum) cultivar(s) having higher waterlogging tolerance is crucial to expanding cotton cultivation in the low-lying areas. The present study was designed to investigate the effect of waterlogging on the reproductive development of four elite upland cotton cultivars, namely, Rupali-1, CB-12, CB-13, and DM-3, against four waterlogging durations (e.g., 0, 3, 6, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 58 publications
0
1
0
1
Order By: Relevance
“…In the context of stress response, proline serves a protective role by directly neutralizing ROS, stabilizing proteins and antioxidant enzymes, maintaining the balance of intra-cellular redox homeostasis (specifically the ratio of NADP + /NADPH and GSH/GSSG), and enhancing cell signaling while safeguarding photosynthetic pigments [ 74 , 75 ]. Several researchers have reported that the increased accumulation of proline in response to waterlogging stress is regarded as a significant biochemical adaptation that serves to mitigate the deleterious consequences of waterlogging, ultimately leading to enhanced plant performance [ 9 , 12 , 37 , 50 , 76 , 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the context of stress response, proline serves a protective role by directly neutralizing ROS, stabilizing proteins and antioxidant enzymes, maintaining the balance of intra-cellular redox homeostasis (specifically the ratio of NADP + /NADPH and GSH/GSSG), and enhancing cell signaling while safeguarding photosynthetic pigments [ 74 , 75 ]. Several researchers have reported that the increased accumulation of proline in response to waterlogging stress is regarded as a significant biochemical adaptation that serves to mitigate the deleterious consequences of waterlogging, ultimately leading to enhanced plant performance [ 9 , 12 , 37 , 50 , 76 , 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…Estudios similares al presente, pero en otras especies, han demostrado que el aumento en la duración de la inundación y la sequía afecta negativamente la conductancia estomática y la tasa fotosintética en la soya (Adegoye et al, 2023), el algodón (Huang et al, 2023;Somaddar et al, 2023), kiwi (Wurms et al, 2023), el maíz (Ru et al, 2023), el fríjol caupí (Pompelli et al, 2022) y el arroz (López-Hernández et al, 2018), entre otros. Los trabajos coinciden en que las plantas son vulnerables a la sequía e inundación, porque reducen considerablemente las tasas de difusión de O 2 y CO 2 en las raíces y tallos, e inhiben significativamente tanto la fotosíntesis como la respiración (Kim et al, 2015).…”
Section: Discussionunclassified